Cold people : a novel - Smith, Tom Rob (Scribner, an imprint of Simon & Schuster, Inc., 2023)
The world has fallen. Without warning, a mysterious and omnipotent force has claimed the planet for their own. There are no negotiations, no demands, no reasons given for their actions. All they have is a message: humanity has thirty days to reach the one place on Earth where they will be allowed to exist, Antarctica.